Changes in Customer Behavior Towards Video Advertising Post-Pandemic - Surjandy, Surjandy; Cassandra, Cadelina (Universitas Airlangga, 2024)
Background: Video Advertising (VI) is a powerful media tool used by several companies as a marketing strategy. During COVID-19 pandemic, there was a wide adoption of digital media, particularly VI, to promote company products. However, some changes occurred post-pandemic, which influenced customer behavior. Objective: This research aimed to explore changes in customer behavior towards VI post-pandemic. The exploration focused on understanding changes in four major factors which included Sensory Appeal (SEN), Informativeness (INF), Entertainment (ENT), and Telepresence (PRE). Methods: Data were collected using snowball sampling method, resulting in 744 responses. After deleting outliers and non-shopping customer, there were 584 analyzable data. Covariance-Based Structural Equation Model (CB SEM) method facilitated by Lisrel Application was used for data analysis. Results: The result showed that significant changes have occurred in customer behavior to VI post-pandemic. Among the 13 tested hypotheses, 11 showed significant influences, while 2 did not, indicating shifts in customer behavior. Conclusion: COVID-19 pandemic led to significant changes and imparted customer with a new understanding of VI, which became a major marketing tool. These changes were due to experiences during the pandemic, which affected SEN (72%), INF (77%), ENT (76%), and PRE (70%). Further analysis showed that ENT affected Customer Trust (CT) and Actual Purchase (APU) by 20% and 27%, while PRE caused 34% and 20% respectively, indicating a decrease in customer response from VI to CT and APU. Based on these results, further exploration should build on the identified factors and investigate additional variables that had not been considered. Keywords: Post-Pandemic, COVID-19, Customer Behavior, Video Advertising